Helicity of perfluoroalkyl chains controlled by the self‐assembly of the Ala‐Ala dipeptides. Issue 11 (29th August 2019) - Zhang, Lianglin; Lin, Shuwei; Tong, Qiyun; Li, Yan; Wang, Yong; Li, Yi; Li, Baozong; Yang, Yonggang
Abstract: Four Ala‐Ala dipeptides with a perfluoroalkyl chain at the N‐terminal were synthesized. They were able to self‐assemble into helical nanofibers and/or twisted nanobelts in a mixture of DMSO/H2 O. The handedness of nanofibers and nanobelts was controlled by the chirality of the alanine at the N‐terminal. The stacking handedness of the phenylene groups and the helicity of the perfluoroalkyl chain were studied using circular dichroism spectroscopy and vibrational circular dichroism, respectively. The chirality of the alanine at N‐terminal controlled the stacking handedness of the neighboring phenylene groups. Moreover, due to the low potential barrier between M‐ and P‐helices of the perfluorocarbon chain, the handedness of the organic self‐assemblies eventually controlled the helicity of the perfluorocarbon chain. X‐ray diffraction indicated that a lamellar structure was formed by the dimers of the dipeptides. Abstract :